2020
DOI: 10.1002/saj2.20009
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐infrared spectroscopy for prediction of soil health indicators in the United States

Abstract: Quantifying the holistic notion of soil health requires a large suite of measurements spanning the physical, chemical and biological properties of soil. The cost of measuring the full suite of soil health indicators via traditional methods is cost prohibitive for the spatial and temporal monitoring many land managers would like. Here we investigated the ability to make predictions of numerous soil health indicators from the large mid‐infrared (MIR) spectral library developed by the National Soil Survey Center.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Hermans et al, 2017). This is analogous to the use of spectral libraries to calibrate infra-red measurements of soil health properties (Sanderman et al, 2020). These measurements use infrared reflectance of soils to correlate with known, measured soil properties, which requires large libraries of spectral signatures across many soil types.…”
Section: Microbes As Bio-indicatorsmentioning
confidence: 99%
“…Hermans et al, 2017). This is analogous to the use of spectral libraries to calibrate infra-red measurements of soil health properties (Sanderman et al, 2020). These measurements use infrared reflectance of soils to correlate with known, measured soil properties, which requires large libraries of spectral signatures across many soil types.…”
Section: Microbes As Bio-indicatorsmentioning
confidence: 99%
“…All samples had measured SOC data, but gaps needed to be filled for other properties. MIR-based predictions, as developed byDangal et al (2019) andSanderman et al (2020), were used to estimate clay content for 277 samples, pH on 170 samples and BD on 3782…”
mentioning
confidence: 99%
“…Although previous studies have reported satisfactory accuracies for C prediction in the POM fraction using MIR spectroscopy (R 2 0.71-0.83), they were carried out in the 0.2-16.8gCkg −1 range of concentration (Janik et al, 2007;Baldock et al, 2018). However, recent studies using heterogeneous soil samples at a country level similarly reported that SOM C and MAOM C were better predicted than POM C (Sanderman et al, 2020). These results can be FIGURE 5 | Scatter plots for predictions of (A) total soil nitrogen (TN), (B) nitrogen content in mineral-associate organic matter (MAOM N) and (C) nitrogen content in particulate organic matter (POM N) resulting from global calibrations from a large-scale dataset using mid infrared spectroscopy and partial least square regression.…”
Section: Prediction Of Soil C and N Pools And Other Soil Propertiesmentioning
confidence: 95%
“…Infrared spectroscopy has been proposed as an alternative method for a rapid determination of soil quality (Seybold et al, 2019) as well as to predict the distribution of SOM fractions (Baldock et al, 2018). Mid-infrared (MIR) spectroscopy combined with chemometrics is a feasible quantitative analysis method in soils (Sanderman et al, 2020). Additionally, MIR provides detailed information about fundamental vibrations of minerals (i.e., quartz -Si-O frequencies) and organic matter (Soriano-Disla et al, 2014).…”
Section: Introductionmentioning
confidence: 99%